Pengaruh Kegiatan Ekstrakurikuler Pramuka Terhadap Kedisiplinan Siswa Kelas X Di SMKN 6 Makassar - Indra Nur Aini; Hariany Idris; Samsinar (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This research aims to determine the influence of scout extracurricular activities on student discipline. The variables in this research are scout extracurriculars as the independent variable and student discipline as the dependent variable. The population of this research was all accounting students in class X at SMKN 6 Makassar. The sampling technique uses Simple Random Sampling technique, samples from the population are obtained from part of the population with a sample of 36 students. The data collection techniques used are observation, questionnaires and documentation. The data analysis techniques used are descriptive percentage analysis, instrument testing and hypothesis testing. Based on the results of the data analysis that has been carried out, the descriptive analysis results for scout extracurricular activities were 66.80 percent which is classified as good and student discipline was 66.05 percent which is classified as good. From the results of a simple linear regression analysis, it was obtained that scout extracurricular Y = 8,434 + 0.896, which means that for every additional 1 scout extracurricular value, the student's discipline score increased by 0.896. The results of the analysis of the coefficient of determination (r2) obtained a value of (r2) = 0.614 or 6%, which means that scout extracurricular activities contributed 6 percent to student discipline and the remaining 94 percent was influenced by other factors. Meanwhile, from the results of the t-test analysis, a significant value of 0.000 <0.05 was obtained, which means that the scout extracurricular variable has a significant effect on student discipline, thus the hypothesis is accepted.